The political ideology of Ayatollah Khamenei out of the mouth of the Supreme Leader of Iran - Hovsepian-Bearce, Yvette (UCLA Center for Middle East Development (CMED), 2016)
"Ayatollah 'Ali Hosseini Khamenei, Supreme Leader of the Islamic Republic of Iran is one of the most controversial and influential Muslim leaders in the world today. As Iran's main decision-maker, his theocratic ideology and decisions carry global consequences. The Political Ideology of Ayatollah 'Ali Hosseini Khamenei is the first book to identify and analyse the ideological framework of the Supreme Leader from 1962 to 2014, using his own writings, speeches and biographical records, and literature published in Iran in their original Farsi. This work provides new insight into Khamenei's political thought and behavior as well as their impact on Iran's policies domestically, regionally and internationally. Correlating the development of Khamenei's personality, character and political behaviour with Iran's internal and external struggles, this study explores key issues of the region, in particular Iran's political posture toward Israel and the United States and the diplomatic crises unfolding over Iran's nuclear development program, as well as providing a comprehensive chronological and thematic survey of Khamenei's life. This book will appeal to students, scholars, researchers and policy-makers of Middle Eastern Politics, Iranian Studies, Islamic Studies, and International Relations, and is an essential resource for those interested in understanding Iran's policies toward Israel, the United States and the Muslim world from the perspectives of its top Leader"--Provided by publisher.